2017
DOI: 10.1002/adfm.201704069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkyl Chain Branching Point on 3D Crystallinity in High N‐Type Mobility Indolonaphthyridine Polymers

Abstract: Herein, this study investigates the impact of branching-point-extended alkyl chains on the charge transport properties of three ultrahigh n-type mobility conjugated polymers. Using grazing incidence wide-angle X-ray scattering, analysis of the crystallinity of the series shows that while π-π interactions are increased for all three polymers as expected, the impact of the side-chain engineering on polymer backbone crystallinity is unique to each polymer and correlates to the observed changes in charge transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Eventually, high hole mobilities of 10.54 and 12.04 cm 2 V −1 s −1 are achieved for the thin films of P58 and P60 , respectively, after thermal annealing. The improvement of thin film crystallinity and enhancement of charge mobility were also reported for DPP‐based polymers P61 – P66 and P84 – P85 , and other semiconducting polymers P67 – P83 by varying the branching point in the side chains. For conjugated polymers P84 – P85 , however, the effect of side alkyl chains with different branching positions on their charge transporting properties is not distinct…”
Section: Alkyl Chains With Different Structuressupporting
confidence: 54%
See 1 more Smart Citation
“…Eventually, high hole mobilities of 10.54 and 12.04 cm 2 V −1 s −1 are achieved for the thin films of P58 and P60 , respectively, after thermal annealing. The improvement of thin film crystallinity and enhancement of charge mobility were also reported for DPP‐based polymers P61 – P66 and P84 – P85 , and other semiconducting polymers P67 – P83 by varying the branching point in the side chains. For conjugated polymers P84 – P85 , however, the effect of side alkyl chains with different branching positions on their charge transporting properties is not distinct…”
Section: Alkyl Chains With Different Structuressupporting
confidence: 54%
“…Branching alkyl chains are usually attached to the donor and/or acceptor moieties of conjugated D–A polymers to improve their solubilities in organic solvents. Many groups have investigated the effect of the branching point position of branching alkyl chain on the solid state structures and charge transporting behaviors of conjugated polymers ( Scheme ) . In most cases, the polymer backbones become more planar, and the interchain packing and charge mobilities are improved after moving the branching points away from the backbones.…”
Section: Alkyl Chains With Different Structuresmentioning
confidence: 99%
“…Moving the branching point of alkyl chains in otherwise identical polymers was conducted to gain insight into structure – function relationships . Polymers P11 – P14 have a branching point relatively close to the polymer backbone making π‐π stacking more challenging.…”
Section: Applicationsmentioning
confidence: 99%
“…During the past few decades, the wettability of polymers on surfaces has evolved as an important topic of research because it critically controls technological applications ranging from fluorescent coatings to sensors, photovoltaic cells and other thin‐film‐based organic electronic devices . The effects of alkyl chain on the nanostructure of polymer films was reported to influence the charge transport properties by increasing carrier mobilities over several orders of magnitude …”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] The effects of alkyl chain on the nanostructure of polymer films was reported to influence the charge transport properties by increasing carrier mobilities over several orders of magnitude. 58 Although the above-mentioned parameters may all affect the dewetting behaviours of polymer films, there can be other dominant factors which are far more complex. Glynos et al demonstrated that the competition between interfacially attractive conformational entropic effects and intermolecular entropic repulsions can markedly control the wetting properties of a polymer.…”
Section: Introductionmentioning
confidence: 99%